The Role of Financial Education Through Storytelling Digital and the Enthusiasm of Saving in Piggy Banks (Case Study: Starkids Kabanjahe Integrated Preschool) - Kaban, Debi Yolanda; Ginting, Rahelya Br; Surbakti, Asprina Br; Br Ginting, Lastri Marsely (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Early childhood education (PAUD) has a very important role in the formation of children's character, because at this age, which is called the golden age, a child's abilities can still be directed and responsive in accepting and responding to their surroundings. Financial education needs to be introduced as early as possible so that children have the right knowledge to manage money well. The habit of saving in a piggy bank is also almost never found in this digital era. The implementation of Community Service activities by the Indonesian Institute of Technology (ITB Indonesia) Kabanjahe Branch campus entitled, "The Role of Financial Education Through Fairy Tales and Enjoying Saving in Piggy Banks (Case Study: Starkids Kabanjahe Integrated PAUD School)", aims to instill the importance of financial education from an early age. The method of implementing this community service is through fairy tales and saving in piggy banks to children at Starkids Kabanjahe Integrated PAUD. The results that can be achieved from the implementation of this community service are that all children at Starkids Kabanjahe Integrated PAUD feel enthusiastic and motivated to save in piggy banks and can understand the meaning of saving.